Effect of intraluminal temperature on human oesophageal motor function - YEGEN, BERRAK (My University, 1998)
Oesophageal motor activity is altered by bolus temperature. The effects of sustained cold or warm intraluminal temperature on oesophageal motility have not been documented in detail. Oesophageal manometry was performed in 11 normal subjects after intraluminal room, cold- and warm-water treatments. The intraluminal temperatures were 34.2 ± 0.8, 30.6 ± 1.7 and 39.7 ± 0.9°C respectively during room temperature, cold and warm applications. Low-temperature treatment prolonged the duration of lower oesophageal sphincter relaxation and the duration of oesophageal peristaltic contraction wave compared with the room temperature and warm treatments. Low temperature also attenuated the mean pressure slope of oesophageal contraction waves and resulted in an increased percentage of non-transmitted and simultaneous contractions. The effects of low-temperature application persisted as long as the intraluminal temperature remained constant and there was no adaptation. Cooling oesophageal lumen temperature alters oesophageal motor activity, and this effect is not adaptive.
Keywords: High temperature; Low temperature; Lower oesophageal sphincter; Oesophageal motility; Room temperature